Isolation and Production of Polysaccharide from Locally Isolated Termitomyces sp. Mushroom - Srivani Sellathoroe; Tengku Shafazila Tengku Saharuddin; Wan Abd Al Qadr Imad Wan-Mohtar; Iffah Izzati Zakaria; Rahayu Ahmad; Ehwan Ngadi (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology